Critical Study Of Digital Library In India (Journal of Namibian Studies : History Politics Culture, 2023)
The exploration of the Digital Library is particularly beneficial to education since it allows students to learn and build a digital library, supports the process of learning through teaching, and assists the university in obtaining catalogs, references, and research-related information. While the results of the topic and sub-topic analysis on the implementation of the public library demonstrate that: the company can create a library and provide information on its products; the public can obtain information more quickly thanks to the implementation of the Digital Library; and the preservation of historical and cultural relics that can be learned from in the future. In this article, critical study of digital library in Indian context has been discussed.